Estudo sobre a inibição da oviposição em Angiostrongylus cantonensis mediada por agonista e antagonista da serotonina - Osório, Joana Borges (2012)
The Angiostrongylus genus includes two species that can infect humans, A. cantonensis and A. costaricensis. They may cause infections known as eosinophilic meningitis and abdominal angiostrongyliasis, respectively. In A. costaricensis infection, eggs and larvae are central elements in the inflammatory reactions, which may get worse with death of the worms. The currently available anthelmintics act on the parasite essential metabolic pathways with a killing effect. Therefore, an alternative substance to treat angiostrongyliasis, acting mainly in worms reproduction is necessary. An in vitro study conducted with Schistosoma mansoni showed inhibition of oviposition by Phenanthroline. In another study with Caenorhabditis elegans, it was shown that serotonin increases the egg-laying rate of the female nematode, besides controlling the change of its posture state (rest and activation). Serotonin is a neurotransmitter present in vertebrates and invertebrates. In order to test the effect on egg laying of Angiostrongylus spp., two substances that interfere with serotonin neurotransmission in humans, Buspirone and Pizotifen, were used in an experimental model in vivo. 28 rodents of species Rattus norvegicus were divided into three groups and infected with 100 L3 of A. cantonensis: a control group (untreated) and two groups treated with each substance. The substances were administered as soon as all rodents started releasing larvae, once a day, orally, for 10 days, at a concentration of 0.03 mg / mL each. In this period rodent feces were collected daily for counting the number of L1 and after 10 days the animals were euthanized for collection of the worms. The average number of larvae released in feces was 37,934 by the Control group, 10,658 by the Buspirone group and 6,658 by the Pizotifen group. The worms were counted and separated by sex: in the Control group 59 females and 40 males were obtained; in Buspirone group 86 females and 41 males were found; and in the Pizotifen group 83 females and 64 males were counted. The comparison of data from Control and Experimental groups was statistically analyzed by ANOVA and no significant difference was observed. Females were measured using a millimetric eyepiece installed in a stereomicroscope. The ANOVA analysis resulted in a significant difference between Control and Pizotifen, which had an average size of 18 mm, compared with to average size of 19 mm of Control, indicating that Pizotifen would have some effect in the nematodes development, but not affecting their reproduction. These results indicate that the search for alternative drugs that act on egg laying needs a better understanding of the pathways that regulate the reproductive system of parasitic organisms.